(3WH GdWjhQs - (3MLGL Hf NjKes ((3YKeGf GdTgjQ HedG GdMdHj s)
(3ChdgG (B:s
(3HYO GdHSedI bGd GdMLGL GHf NjKe GSJNQLfG ef NRGfI GdQTjO gPG GdcJGH hYQVfGg Ydi GdZWQja GHf bOeGeI GdZSGfj aYQaI hPcQ Cf eYGP Hf eSde RGOge ajg s
(3BNQgG (B:s
(3hGYde CfeG jDJj GdWjQ aj Pdc ef HGR EeG jCNP EWYGeI Edi GdYTGA Ch HWYeg hVjaJg Edj HGdaOGI s
(3fSNI NRGFfjI QSe GdeMOhej eG fUhg s
(3hJhLO ef fSNJjf (B161 (3, (B172 - (3WH GdeYgO s
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs